Qawa'id Fiqhiyyah sebagai Pilar Konseptual Pengembangan Ekonomi Syariah - Mawardi Dalimunthe (Program Studi Magister Hukum Islam - UIN Bukittinggi, 2025)
The development of Islamic economics demands adaptive legal regulations to address new issues not explicitly addressed in the Qur'an and Hadith. Islamic jurisprudence (qawa'id fiqhiyyah) serves as a crucial legal basis for establishing and interpreting Islamic economic law to ensure its adherence to Islamic principles. This is crucial for strengthening justice, transparency, and sustainability in Islamic economics. This study aims to examine the role of Islamic jurisprudence (qawa'id fiqhiyyah) as a conceptual pillar in the development of Islamic economics, focusing on how Islamic legal principles within these principles serve as a normative basis for formulating economic policies and practices that align with Islamic values. The method used is a qualitative jurisprudential-normative approach through a literature review of classical and contemporary literature. The results of this study indicate that Islamic jurisprudence facilitates the interpretation and enforcement of laws for modern economic transactions, guarantees the validity of contracts, protects ownership rights, and promotes justice, accountability, and transparency in Islamic economics. The implication of this research is that the application of Islamic jurisprudence as a normative framework can strengthen the governance of Islamic financial institutions, assist in the formulation of equitable economic policies, and encourage innovation in financial products in accordance with Islamic principles that are adaptive to the dynamics of the times. Thus, Islamic jurisprudence is a vital instrument in maintaining the integrity and sustainability of the Islamic economy while simultaneously increasing public trust and sustainable Islamic financial inclusion. Perkembangan ekonomi syariah menuntut aturan hukum yang adaptif untuk mengatasi persoalan baru yang belum diatur secara eksplisit dalam Al-Qur’an dan Hadits. Qawa’id fiqhiyyah menjadi landasan hukum penting untuk menetapkan dan menafsirkan hukum ekonomi syariah agar tetap sesuai prinsip syariah. Hal ini krusial untuk memperkuat keadilan, transparansi, dan keberlanjutan dalam ekonomi syariah. Penelitian ini bertujuan untuk mengkaji peran qawa’id fiqhiyyah sebagai pilar konseptual dalam pengembangan ekonomi syariah, sekaligus menawarkan suatu kerangka konseptual berupa sintesis kaidah-kaidah fiqhiyyah yang relevan bagi ekonomi syariah kontemporer. Kebaruan penelitian ini terletak pada sintesis qawa’id fiqhiyyah muamalah sebagai kerangka normatif sistematis bagi pengembangan ekonomi syariah kontemporer. Metode yang digunakan adalah kualitatif dengan pendekatan yuridis-normatif melalui studi pustaka dari literatur klasik dan kontemporer. Hasil penelitian ini menunjukkan bahwa qawa’id fiqhiyyah memberikan kemudahan dalam menafsirkan dan menetapkan hukum terhadap transaksi ekonomi modern, menjamin keabsahan akad, melindungi hak kepemilikan, dan mendorong keadilan, tanggung jawab, serta transparansi dalam ekonomi Islam. Implikasi dari penelitian ini adalah penerapan kaidah fiqh sebagai kerangka berpikir normatif dapat memperkuat tata kelola lembaga keuangan syariah, membantuk perumusan kebijakan ekonomi berkeadilan, serta mendorong inovasi produk keuangan sesuai prinsip syariah yang adaptif terhadap dinamika zaman. Dengan demikian, qawa’id fiqhiyyah menjadi instrumen vital dalam menjaga integritas dan keberlanjutan ekonomi syariah sekaligus meningkatkan kepercayaan publik dan inklusi keuangan syariah secara berkelanjutan.